Migrations, transferts et réécritures :le destin des monuments publics d’Algérie après l’Indépendance - Claire Garcia (Les Cahiers de l'École du Louvre)
Studying the installation of public monuments during French colonisation and their evolution after the independence of Algeria makes one question, to start with, the meaning of the commemoration within a territory. With regard to the definition given by geographers of the term territory, the monument is a sort of material projection of the territory incarnating its essence: identity, social and economic. Territory and monument are thus inseparable. First, we will study the monuments installed in Algeria during colonisation and we will examine the memory that they convey. What is significance for Algerians of the installation of monuments commemorating the great men of the history of France? Faced with a destiny as diverse as destruction, concealment or “repatriation” from Algeria to France, what events do these monuments commemorate now? Does a second installation in metropolitan France offer a second life or is it a rewriting of history?